Demonstration of the cellular viability and safety of Enterococcus faecium CRL 183 in long-term experiments - Cano, Veridiana P. S.; Valentini, Sandro Roberto [UNESP]; Sivieri, Katia [UNESP]; Rossi, Elizeu Antonio [UNESP] (Edp Sciences S A, 2007)
Enterococcus faecium CRL 183, a strain isolated from NSLAB cheese starter, has been the focus of much research on its potential probiotic capacity, although its survival through the gastrointestinal tract has not been demonstrated so far. In order to determine the capacity of E. faecium CRL 183 to survive such conditions, this strain was administered daily to rats for 30 weeks. The experimental animals were divided into Group I: those that did not receive E. faecium, Group II: those that received a pure culture of E. faecium CRL 183 and Group III: animals that received E. faecium CRL 183 in the form of a fermented soy-based product. Faecal samples were collected at the beginning and at the 50%, 75% and 100% stages of the experimental period. Isolation and counts of Enterococcus were carried out on KF selective media. To distinguish the various Enterococcus species in the faeces, biochemical (API Strep 20) and molecular (PCR) tests were performed. Initially, E. faecium was absent from the intestinal flora of the rats; however, after 15 weeks of administration, E. faecium could be recovered from the faeces of Groups II and III, demonstrating that E. faecium CRL 183 was able to survive gastrointestinal transit under the study conditions. This is further evidence of the probiotic qualities of this strain. The safety of the strain was also investigated with regard to body weight and serum biochemical analysis.
Keywords: probiotic; Enterococcus faecium; rat; survival